Oil shocks and endogenous markups: results from an estimated euro area DSGE model - Marcelo Sánchez (European Central Bank (ECB), 2008)
This paper estimates a linearised DSGE model for the euro area. The model is New Keynesian and allows for a role for oil usage and endogenous price markups. We find that the price markup reacts positively to the ratio of expected discounted profits to current output, which is normally seen to give rise to a "countercyclical" markup. The importance of shocks to monetary policy and oil prices is estimated to have declined in the post-1990 period, in line with the higher predictability of policy and the fall in the persistence and - to a lesser extent - variability of oil disturbances. Counterfactual exercises show that oil efficiency gains would alleviate the inflationary and contractionary consequences of oil shocks, while higher wage flexibility would help ease the impact on real output at the expense of wider fluctuations in inflation. Finally, the rise in price markups induced by an oil disturbance is not found to considerably amplify the inflationary and contractionary effects of the shock.
Keywords: C15; E31; E32; E37; 330; endogenous markup; estimated DSGE models; euro area; oil shocks; Ölpreis; Mark-up Pricing; Wirkungsanalyse; Dynamisches Gleichgewicht; EU-Staaten